Association Between Serum Folic Acid Levels and Type 2 Diabetes Mellitus in Overweight or Obese Patients: A Retrospective Study - Dai Y; Guo M; Xiong J; Jiang L (Diabetes, Metabolic Syndrome and Obesity)
Yaji Dai,1,* Mingfei Guo,2,* Jianglei Xiong,1 Lei Jiang1 1Department of Pharmacy, Anhui No.2 Provincial People’s Hospital, Hefei, Anhui, People’s Republic of China; 2Department of Scientific Research, The First Affiliated Hospital of Anhui Medical University, Anhui Public Health Clinical Center, Hefei, Anhui, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lei Jiang, Department of Pharmacy, Anhui No.2 Provincial People’s Hospital, Hefei, Anhui, People’s Republic of China, Email 13155192069@163.comPurpose: The relationship between folic acid (FA) levels and type 2 diabetes mellitus (T2DM) with overweight or obesity remains uncertain. This study aimed to further investigate the relationship between them.Methods: A retrospective study was conducted on 149 patients, comprising 64 patients with T2DM and normal weight and 85 patients with T2DM and overweight or obese status.Results: Our findings revealed significantly lower levels of FA and neutrophil-to-lymphocyte ratio (NLR) in overweight/obese T2DM patients compared to their normal-BMI counterparts (P < 0.001). The overweight/obese cohort exhibited elevated metabolic parameters, including fasting C-peptide, serum uric acid, total cholesterol (TC), triglycerides (TG), and very low-density lipoprotein cholesterol (VLDL-C) levels (P < 0.05). Notably, correlation analysis demonstrated a significant positive association between FA levels and both age (r = 0.341, P < 0.001), diabetes duration (r = 0.278, P = 0.001), and NLR (r = 0.212, P = 0.009). Conversely, inverse correlations were observed between FA levels and C-peptide (r = − 0.240, P = 0.004), TG (r = − 0.254, P < 0.001), and VLDL-C (r = − 0.271, P = 0.001).Conclusion: This research found that FA levels were significantly associated with T2DM in individuals who were overweight or obese.Keywords: T2DM, folic acid, overweight, obesity